Functional Graphene Oxide as a Nanocarrier for Controlled Loading and Targeted Delivery of Mixed Anticancer Drugs - Zhang, Liming; Xia, Jingguang; Zhao, Qinghuan; Liu, Liwei; Zhang, Zhijun (Small (Weinheim an der Bergstrasse, Germany), 2010)
A simple synthetic route for the preparation of functional nanoscale graphene oxide (NGO), a novel nanocarrier for the loading and targeted delivery of anticancer drugs, is reported. The NGO is functionalized with sulfonic acid groups, which render it stable in physiological solution, followed by covalent binding of folic acid (FA) molecules to the NGO, thus allowing it to specifically target MCF‐7 cells, human breast cancer cells with FA receptors. Furthermore, controlled loading of two anticancer drugs, doxorubicin (DOX) and camptothecin (CPT), onto the FA‐conjugated NGO (FA–NGO) via π–π stacking and hydrophobic interactions is investigated. It is demonstrated that FA–NGO loaded with the two anticancer drugs shows specific targeting to MCF‐7 cells, and remarkably high cytotoxicity compared to NGO loaded with either DOX or CPT only. Considering that the combined use of two or more drugs, a widely adopted clinical practice, often displays much better therapeutic efficacy than that of a single drug, the controlled loading and targeted delivery of mixed anticancer drugs using these graphene‐based nanocarriers may find widespread application in biomedicine. Nanoscale graphene oxide (NGO) with good biocompatibility and physiological stability is synthesized by functionalization with sulfonic acid groups and conjugation with folic acid. In the delivery of multiple drugs, cellular‐uptake experiments show the targeted delivery of the anticancer drugs doxorubicin and camptothecin into cells (see picture) by the NGO via receptor‐mediated endocytosis.